Reseliensi Warga Desa Pendung Talang Genting Pasca Konflik Dengan Warga Desa Sleman Kabupaten Kerinci - Iranda, Agung (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Abstract: Conflicts in Indonesia do not only occur at the regional, ethnic and religious level but also at the village level. One example is the inter-village conflict between Pentagen and Sleman village residents in Kerinci District, Jambi Province. Conflicts between villages have caused huge losses both materially and psychologically. In such catastrophic conditions, residents attempt to be resilient and rebuild their life orientations. This study used qualitative method with phenomenological approach. In-depth interviews with 5 Pentagen villagers who were victims of the conflict were conducted to gather data. Data analysis used interpretative phenomenology analysis. The results of the study revealed the existence of resilience character in Pentagen residents in the forms of emotional regulation, impulse control, optimism, causal analysis, and self-efficacy. The novelty of these findings is the existence of themes related to a sense of kinship and togetherness, prosocial attitude, trauma healing, evacuation, and life orientation. Factors that influence resilience are religiosity, family encouragement, and social support.